2021
DOI: 10.3847/2041-8213/abe1b4
|View full text |Cite
|
Sign up to set email alerts
|

NICER Discovery of Millisecond X-Ray Pulsations and an Ultracompact Orbit in IGR J17494-3030

Abstract: We report the detection of 376.05 Hz (2.66 ms) coherent X-ray pulsations in NICER observations of a transient outburst of the low-mass X-ray binary IGR J17494−3030 in 2020 October/November. The system is an accreting millisecond X-ray pulsar in a 75 minute ultracompact binary. The mass donor is most likely a 0.02 M finite-entropy white dwarf composed of He or C/O. The fractional rms pulsed amplitude is 7.4%, and the soft (1-3 keV) X-ray pulse profile contains a significant second harmonic. The pulsed amplitude… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Other potential dual-line sources are the nearby (d 5 kpc and d ∼ 3.3 kpc, respectively) X-ray bursters 2S 0918-549 and 4U 1543-624 -UCXBs with ≈ 17.4 and ≈ 18.2 minute orbital periods, respectively (Zhong & Wang 2011;Ludlam et al 2019) -though little is known about the NSs. Ng et al (2021) recently reported the discovery of X-ray pulsations in IGR J17494-3030, inferring that the source is a 3 ms AMXP in a 75 min binary. A secular spindown of this object was measured as νJ17494 spin = −2.1 × 10 −14 Hz s −1 , implying a maximum mass quadrupole Q max 22 ≈ 8.9 × 10 36 g cm 2 (Bildsten 1998), potentially detectable by ET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other potential dual-line sources are the nearby (d 5 kpc and d ∼ 3.3 kpc, respectively) X-ray bursters 2S 0918-549 and 4U 1543-624 -UCXBs with ≈ 17.4 and ≈ 18.2 minute orbital periods, respectively (Zhong & Wang 2011;Ludlam et al 2019) -though little is known about the NSs. Ng et al (2021) recently reported the discovery of X-ray pulsations in IGR J17494-3030, inferring that the source is a 3 ms AMXP in a 75 min binary. A secular spindown of this object was measured as νJ17494 spin = −2.1 × 10 −14 Hz s −1 , implying a maximum mass quadrupole Q max 22 ≈ 8.9 × 10 36 g cm 2 (Bildsten 1998), potentially detectable by ET.…”
Section: Discussionmentioning
confidence: 99%
“…A secular spindown of this object was measured as νJ17494 spin = −2.1 × 10 −14 Hz s −1 , implying a maximum mass quadrupole Q max 22 ≈ 8.9 × 10 36 g cm 2 (Bildsten 1998), potentially detectable by ET. The donor star is quite light however, Mcomp ∼ 10 −2 M (Ng et al 2021), and the source is likely out of view for LISA.…”
Section: Discussionmentioning
confidence: 99%
“…Ultra-compact X-ray binaries (UCXBs) are a sub-class of LMXBs that are characterised by orbital periods shorter than 80 min and a hydrogen-deficient donor star, such as a nondegenerate helium star or a white dwarf (Nelson et al 1986;Savonije et al 1986; for a review, see Nelemans & Jonker 2010). Currently, there are 24 known UCXBs with a measured orbital period and a further 15 systems have been classified as candidate UCXBs (Sazonov et al 2020;Ng et al 2021). To date, all confirmed UCXBs have been found to harbour a NS accretor, while for some candidates the nature of the accretor has not been established conclusively (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several thousand bursts have been observed to date (see, e.g., Galloway et al 2008Galloway et al , 2020. However, seven sources (including Swift J1756.9−2508) out of 21 known AMXPs, including twenty AMXPs mentioned in Table 1 from Di Salvo & Sanna (2020) and the newly confirmed AMXP IGR J17494−3030 (Ng et al 2021), have not showed type-I X-ray bursts during their outbursts. Hence, the distance to Swift J1756.9−2508 is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…9.The assumption of a Roche lobe-filling companion implies a mass-radius relation R c = 0.082 (M c /0.1M ) 1/3 (P orb /40 min) 2/3 R , shown in logarithmic scale for different AMXPs with orbital periods around 40 min. From bottom up, the sources are IGR J17062−6143(Strohmayer et al 2018), XTE J1807−294(Campana et al 2003), XTE J1751−305(Papitto et al 2010), XTE J0929−314(Galloway et al 2002), MAXI J0911−655(Sanna et al 2017), IGR J16597−3704(Sanna et al 2018a), Swift J1756.9−2508(Krimm et al 2007b), NGC 6440 X-2(Altamirano et al 2010), IGR J17494−3030(Ng et al 2021), HETE J1900.1−2455(Kaaret et al 2006), IGR J17379−3747(Sanna et al 2018b), SAX J1808.4−3658(Wijnands & van der Klis 1998) and IGR J00291+5934(Galloway et al 2005). The magenta dashed lines show the AMXPs with detected type-I X-ray bursts, while the green dashed lines show the AMXPs without type-I X-ray bursts.…”
mentioning
confidence: 99%